Managing consultants : consultancy as the management of impressions - Clark, Timothy (Buckingham : Open University Press, 1995)
Introduction. The management consultancy market. The characteristics of management consultancy services. Choosing a management consultant. The dramaturgical metaphor. Consultancy as impression management.
Keywords: Management; Business consultants; Management; Business consultants -- Great Britain; Management -- Great Britain; Business consultants